Formability study of bake hardening steel and its correlation with microstructure. (May 2022) - Das, Atanu; Kumar, Basant; Ahmed, Sheikh N; Paul, Surajit Kumar; Mandal, Gopi K
In the present study, the bake hardening (BH 240) steel sheet's formability behavior is studied experimentally based on the Nakajima test method. A forming limit diagram is successfully constructed using universal sheet metal forming machine by offline measuring the strains of deformed specimens. In-process strain measurement based on a digital image correlation technique is also performed for a few selected samples to compare the results with manual strain measurement techniques. All the deformed specimens are also characterized to correlate the sample geometries with hardness values and microstructure. It is observed that the hardness value gradually decreases with an increase in sample width for all the deformed specimens up to the width of 150 mm, except for full-width sample of 200 mm. Microstructural analysis reveals that the morphology of ferrite grains changes with the sample geometry in all the deformed specimens. Microstructural characterization at the top surface of the specimen demonstrates that the aspect ratio of grains is maximum for a 25 mm width sample due to uni-axial stretching. It is also noted that grain's aspect ratio is close to one (minimum) for a 200 mm width sample due to almost equi-biaxial elongation in grains. It is also observed that the aspect ratio of grains obtained from specimen cross-section indicates that the ratio increases gradually from 25 to 200 mm width samples.